Tn2008-driven carbapenem resistance in Acinetobacter baumannii isolates from a period of increased incidence of infections in a Southwest Virginia hospital (USA). (March 2018) - Rao, Jayasimha; Susanti, Dwi; Childress, Johnathon C.; Mitkos, Michael C.; Brima, Joshua K.; Baffoe-Bonnie, Anthony W.; Pearce, Samuel N.; Grgurich, Dale; Fernandez-Cotarelo, Maria Jose; Kerkering, Thomas M.; Mukhopadhyay, Biswarup
Highlights: Outbreak of carbapenem-resistant multidrug-resistant (MDR) A. baumannii infections in a tertiary care hospital in Virginia. Plasmid-borne Tn 2008 was responsible for carbapenem resistance in MDR A. baumannii outbreak strains. Similar strains were sporadically encountered in the hospital. The other carbapenem resistance determinant in A. baumannii isolated from sporadic infections was IS Aba1 – bla OXA-66 . Abstract: Objectives: The objectives of this study were (i) to determine the genetic basis for carbapenem resistance in multidrug-resistant (MDR) Acinetobacter baumannii strains isolated from patients affected by a sudden increase in the incidence of infections by such organisms in a tertiary care hospital in Virginia, USA, in 2009–2010 and (ii) to examine whether such strains are commonly encountered in the hospital setting. Methods: The whole genomes of one outbreak strain as well as one carbapenem-resistant and one carbapenem-sensitive strain from sporadic infections in 2010–2012 were sequenced and analysed. Then, 5 outbreak isolates and 57 sporadic isolates (of which 39 were carbapenem-resistant) were screened by PCR for relevant DNA elements identified in the genomics investigation. Results: All three strains for which whole-genome sequences were obtained carried resistance genes linked to MDR phenotypes and a ca. 111-kbp plasmid (pCMCVT Ab 1) without drug resistance genes. Of these, the two carbapenem-resistant strains possessed a ca. 74-kbp plasmid (pCMCVT Ab 2) carrying a Tn 2008 transposon that provides high-level carbapenem resistance. PCR analysis showed that all of the outbreak isolates carried both plasmids and Tn 2008, and of the sporadic isolates 88% carried pCMCVT Ab 1, 25% contained pCMCVT Ab 2 and 50% of the latter group carried Tn 2008 . Conclusions: Carbapenem resistance in outbreak strains and 12% of sporadic isolates was due to the pCMCVT Ab 2-borne Tn 2008 . This is the first report of a Tn 2008 -driven outbreak of carbapenem-resistant A. baumannii infections in the Commonwealth of Virginia, which followed similar cases in Pennsylvania and Ohio.